The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ijerph19074004
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Physical Activity and Psychological Well-Being in Non-Athletes and Martial Art Athletes during the COVID-19 Pandemic

Abstract: Background: The objectives of this study were to identify which of the sociodemographic variables affected psychological well-being in two populations that differed in their sports practice at the end of the COVID-19 lockdown in Colombia. Methods: The study was conducted through an online survey using the IPAQ-S and PGWBI-S questionnaires six months after the first SARS-CoV-2 lockdown, between 8 and 22 September 2020 in Colombia. The total number of study participants was 582, subdivided into two groups: (i) n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 49 publications
(73 reference statements)
2
15
0
Order By: Relevance
“…Our results are consistent with previous findings that showed gender-related poor mental health in athletes [ 44 ], the general population [ 45 ], and university students [ 10 ], with females being more affected than males [ 39 ]. However, some body of evidence did not find gender-related differences in psychological suffering [ 8 , 46 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are consistent with previous findings that showed gender-related poor mental health in athletes [ 44 ], the general population [ 45 ], and university students [ 10 ], with females being more affected than males [ 39 ]. However, some body of evidence did not find gender-related differences in psychological suffering [ 8 , 46 ].…”
Section: Discussionsupporting
confidence: 93%
“…With regards to the sex factor, the lockdown affected both male and female participants in the student and employee groups, with females being more affected ( Figure 2 D). In this respect, our results are consistent with other reports [ 8 , 39 ], although they are a discrepancy with previous studies [ 2 ]. Perhaps men and women in our study had different motivations, and the environment had a stronger influence on one gender over the other.…”
Section: Discussionsupporting
confidence: 70%
“…With decreased physical activity, the mental health of the general population was affected by the COVID-19 lockdown, leading to reduced psychological well-being and increased depression, anxiety, and insomnia [13,14]. A study conducted six months after the lockdown revealed that student athletes were less affected by COVID-19 than general students, reporting higher mental health scores on the Psychological General Well-Being Index-Short version [15]. Additionally, athletes competing in higher levels of competition were less anxious and more adaptive than athletes competing in lower levels of competition regarding changes in psychiatric symptoms just after the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrated small relative changes in physical activity for the population subgroups. Large differences in absolute values of physical activity between elite athletes and general adults existed, while the former still exhibited higher levels of physical activity than general adults during the lockdown period (Monterrosa Quintero et al, 2022 ; Shokri et al, 2022 ). Physical activity has been proven to improve sleep quality and mental health (Werneck and Carvalho, 2020 ), and some studies suggest that COVID-19 led to physical activity restriction, which may have led to changes in acute endocrine and metabolic profiles (Uchida et al, 2012 ), and thus inducing the decline in sleep quality.…”
Section: Discussionmentioning
confidence: 99%